Influence of Sex on Students’ Study Orientation at Secondary Level - Biswas, Shyamal Kumar (Advances in Social Sciences Research Journal, 2015)
The influence of sex on students’ study orientation at secondary level was compared and measured through a modified Study Orientation Scale (SOS), which consists 52 items on different aspects of study habit. The study was conducted in the year 2014 for obtaining data of students’ study orientation. The scale was administered on the sample of 360 students those were studying in class X in different schools of Purulia district. Similarly, academic achievement was measured through marks obtained by the students in the school level examination of class IX. The analysis of data revealed that the boys and girls have average level study orientation. The girls are slightly better than the boys in respect of their study orientation. The study also revealed that sex doesn’t show any significant influence on students’ study orientation in secondary schools.